PENGARUH PROFITABILITAS, LEVERAGE, KEPEMILIKAN INSTITUSIONAL, DAN UKURAN PERUSAHAAN TERHADAP PENGHINDARAN PAJAK - Yolanda Abigail Hartanto; Tony Sudirgo (Jurnal Paradigma Akuntansi, 2023)
The purpose of this study was to identify the effect of profitability, leverage, institutional ownership, and firm size on tax avoidance. The data used in this study are manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2019 using eview version 10. This study uses purposive sampling as the sampling technique and uses 84 manufacturing companies as research samples. The results of this study conclude that firm size has a significant positive effect on tax avoidance, while profitability, leverage and institutional ownership do not have a significant effect on tax avoidance. The implication of this research is to know the factors that influence tax avoidance.